2012
DOI: 10.1115/1.4006013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Channel Orientation on the Heat Transfer Coefficient in the Smooth and Dimpled Rotating Rectangular Channels

Abstract: The detailed distribution of the heat transfer coefficient on rotating smooth and dimpled rectangular channels were measured using the transient liquid crystal technique. The rotating speed of the channel was fixed at 500 rpm and the tested Reynolds number based on the channel hydraulic diameter was 10,000. A stationary surface and two different channel rotating orientations of 90 deg and 120 deg were tested in order to investigate the effects of channel orientation on the distribution of the heat tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Inferring the buoyancy mechanisms in the rotating channels from the mixed free convection driven by earth gravity, the buoyancy effects in the rotating ribbed channels with radially outward and inward flows were previously found analogical to the mixed convection in the static channels with counter and parallel flows respectively [1,2,30]. By normalizing the Nu data collected from the rotating surfaces to the similar non-rotating references (Nu 0 ), it is consistently found that the degrees of Bu effects on Nu/Nu 0 ratios are systematically weakened as Ro increases [8,9,11,12,[15][16][17][18][19][20][21][22][27][28][29]; hence ensuring the interdependent Ro and Bu impacts on heat transfer performances in rotating channels.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Inferring the buoyancy mechanisms in the rotating channels from the mixed free convection driven by earth gravity, the buoyancy effects in the rotating ribbed channels with radially outward and inward flows were previously found analogical to the mixed convection in the static channels with counter and parallel flows respectively [1,2,30]. By normalizing the Nu data collected from the rotating surfaces to the similar non-rotating references (Nu 0 ), it is consistently found that the degrees of Bu effects on Nu/Nu 0 ratios are systematically weakened as Ro increases [8,9,11,12,[15][16][17][18][19][20][21][22][27][28][29]; hence ensuring the interdependent Ro and Bu impacts on heat transfer performances in rotating channels.…”
Section: Introductionmentioning
confidence: 80%
“…Such isolated Coriolis force effects generate the peripheral heat transfer decays from the unstable toward the stable walls and are reconfirmed by the heat transfer data converted from the mass transfer test results [24] with diminished buoyancy interaction. Acting by the Coriolis force effects in isolation by increasing Ro, the heat transfer rates over the unstable wall keep increasing from the stationary channel levels; whereas the stable counterparts are initially reduced from the stationary references but followed by the subsequent heat transfer recoveries after Ro exceeding the critical values [1][2][3][4][5][6][8][9][11][12][15][16][17][18][19][20][21][22]. As the near-wall flow structures are considerably affected by the presence of the various types of HTE devices, the Bu impacts on endwall Nu vary with the thermal boundary conditions [25] and the HTE devices [26].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Their data suggested that the channel orientation had more obvious influences on the leading wall than the trailing one. More recently, Kim et al [17] investigated a narrow (AR ¼ 4) smooth and dimpled rotating channel with two different orientations (b ¼ 90 and 120 ) by means of the transient liquid crystal technique. They observed great spanwise heat-transfer variations.…”
Section: Rotating Rectangular Channelsmentioning
confidence: 99%
“…They observed a primary vortex pair shed periodically from the center of each dimple, and two additional secondary vortex pair formed near the spanwise edges of each dimple. Kim et al [5] carried out experiments on the detailed heat transfer coefficients in a rotating smooth and dimpled rectangular channel by means of the TCL (transient liquid crystal) technique. Results show that the heat transfer coefficient on the trailing surface is higher than that on the leading surface.…”
Section: Introductionmentioning
confidence: 99%